Estrategias de integración de los padres de familia en el proceso educativo de estudiantes de básica primaria (2019)
The integration of parents into the educational process of their children is affected by a many reasons, including the disinterest that some parents show to the institutional processes developed in the school, and the lack of motivation teachers and teaching managers offer and to involve these parents in the processes. In one way or another, it is necessary to understand that an individual's academic training is not the sole responsibility of the school in which they are located. Therefore, it can be said that education is built together, taking into account the following dimensions: student, family, and school. The main purpose of this research is to propose strategies for integrating parents in the educational process of primary basic education students of the Institucion Educativa Tecnico Agropecuario de Luruaco. The research is theoretically supported mainly by the postulates exposed by Zabalza (2015), and Razeto (2016) in the category of integration of parents and the premises of Tunnerman (2011), and De Zubiría (2006) in the category of educational processes. It is based on the qualitative epistemological approach, with a non-experimental transactional design, under descriptive-purpose research, being used as instruments for the collection of information, observation and interview, applied, to parents and teachers of the institution. With which it was concluded that the school has the perception of joint work with parents because they attend meetings of the delivery of academic reports, respond to calls of attention of students with difficulty, or because they support commitments at home. However, it was also concluded that parents are mostly willing to work hand-in-hand with teachers and teachers, in turn, have ideas and means to achieve this, so as a result of this research, five strategies are proposed that will allow the family-school integration.